Prescribed Versus Preferred Intensity Resistance Exercise in Fibromyalgia Pain - da Cunha Ribeiro, Roberta P.; Franco, Tathiane C.; Pinto, Ana J.; Pontes Filho, Marco A. G.; Domiciano, Diogo S.; de Sá Pinto, Ana L.; Lima, Fernanda R.; Roschel, Hamilton; Gualano, Bruno (Frontiers in Physiology, 2018)
Exercise is the treatment of choice for fibromyalgia (FM), but little is known about resistance exercise prescription to modulate pain in this condition. This study aimed to compare the effects of different resistance exercise models, comprising self-selected or prescribed intensity, on pain in FM patients. In a cross-over fashion, 32 patients underwent the following sessions: i) standard prescription (STD; 3x10 repetitions at 60% of maximal strength); ii) self-selected load with fixed number of repetitions (SS); iii) self-selected load with volume load (i.e., load x sets x repetitions) matched for STD (SS-VM); and iv) self-selected load with a free number of repetitions until achieving score 7 of rating perceived exertion (SS-RPE). Pain, assessed by Visual Analogic Scale (VAS) and Short-Form McGill Pain Questionnaire (SF-MPQ), was evaluated before and 0, 24, 48, 72 and 96h after the sessions. Load was significantly lower in SS, SS-VM, SS-RPE than in STD, whereas rating perceived exertion and volume load were comparable between sessions. VAS scores increased immediately after all sessions (p<0.0001), and reduced after 48, 72, 96h (p<0.0001), remaining elevated compared to pre-values. SF-MPQ scores increased immediately after all exercise sessions (p=0.025), then gradually reduced across time, reaching baseline levels at 24h. No significant differences between sessions were observed. Both prescribed and preferred intensity resistance exercises failed in reducing pain in FM patients. The recommendation that FM patients should exercise at preferred intensities to avoid exacerbated pain, which appears to be valid for aerobic exercise, does not apply to resistance exercise.